Glutamatergic Neurometabolite Levels in Patients With Ultra-Treatment-Resistant Schizophrenia: A Cross-Sectional 3T Proton Magnetic Resonance Spectroscopy Study - Iwata, Yusuke; Nakajima, Shinichiro; Plitman, Eric; Caravaggio, Fernando; Kim, Julia; Shah, Parita; Mar, Wanna; Chavez, Sofia; De Luca, Vincenzo; Mimura, Masaru; Remington, Gary; Gerretsen, Philip; et al. (Biological psychiatry (1969), 2019)
In terms of antipsychotic treatment response, patients with schizophrenia can be classified into three groups: 1) treatment resistant to both non-clozapine (non-CLZ) antipsychotics and CLZ (ultra-treatment-resistant schizophrenia [URS]), 2) treatment resistant to non-CLZ antipsychotics but CLZ-responsive schizophrenia [non-URS]), and 3) responsive to first-line antipsychotics (non-treatment-resistant schizophrenia). This study aimed to compare glutamatergic neurometabolite levels among these three patient groups and healthy control subjects using proton magnetic resonance spectroscopy. Glutamate and glutamate+glutamine levels were assessed in the caudate, the dorsal anterior cingulate cortex (dACC), and the dorsolateral prefrontal cortex using 3T proton magnetic resonance spectroscopy (point-resolved spectroscopy, echo time = 35 ms). Glutamatergic neurometabolite levels were compared between the groups. A total of 100 participants were included, consisting of 26 patients with URS, 27 patients with non-URS, 21 patients with non-treatment-resistant schizophrenia, and 26 healthy control subjects. Group differences were detected in ACC glutamate+glutamine levels (F3,96 = 2.93, p = .038); patients with URS showed higher dACC glutamate+glutamine levels than healthy control subjects (p = .038). There were no group differences in the caudate or dorsolateral prefrontal cortex. Taken together with previous studies that demonstrated higher ACC glutamate levels in patients with treatment-resistant schizophrenia, this study suggests that higher levels of ACC glutamatergic metabolites may be among the shared biological characteristics of treatment resistance to antipsychotics, including CLZ.